2011
DOI: 10.1016/j.visres.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spatial and binocular summation for motion direction discrimination in strabismic amblyopia

Abstract: Amblyopia is characterised by visual deficits in both spatial vision and motion perception. While the spatial deficits are thought to result from deficient processing at both low and higher level stages of visual processing, the deficits in motion perception appear to result primarily from deficits involving higher level processing. Specifically, it has been argued that the motion deficit in amblyopia occurs when local motion information is pooled spatially and that this process is abnormally susceptible to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…In amblyopia, the deficits at the M-cell level should result in lower sensitivity at both local and global processing stages. But our results and a wide range of studies 13,14,17,41 suggest that the deficits in the motion domain are restricted mostly to the global processing level. Another explanation for the dorsal stream vulnerability in development disorders is due to the late development of the dorsal stream compared with the ventral stream functions.…”
Section: Comparison Of the Global Motion And Form Deficits In Amblyopiamentioning
confidence: 38%
See 1 more Smart Citation
“…In amblyopia, the deficits at the M-cell level should result in lower sensitivity at both local and global processing stages. But our results and a wide range of studies 13,14,17,41 suggest that the deficits in the motion domain are restricted mostly to the global processing level. Another explanation for the dorsal stream vulnerability in development disorders is due to the late development of the dorsal stream compared with the ventral stream functions.…”
Section: Comparison Of the Global Motion And Form Deficits In Amblyopiamentioning
confidence: 38%
“…The normal internal equivalent noise suggests that local motion processing is intact in both types of amblyopia, in agreement with other studies. 13,14,17,41 The direction sensitive cells stimulated by the amblyopic eye in V1 are also reported to be normal in anisometropic and strabismic primates. 40 Our finding of abnormal global processing in strabismic amblyopia is supported by previous physiological and imaging studies that reported a reduced contribution from the amblyopic eye to extra striate motion areas (MT, MST).…”
Section: 40mentioning
confidence: 98%
“…A univariate ANOVA conducted on the dichoptic suppression mapping measurements showed significant effects of eccentricity (F [4,88] ¼ 9.284, P < 0.001). Our data showed that there were significant differences among five eccentricities.…”
Section: Distribution Characteristics Of Interocular Suppression Amonmentioning
confidence: 99%
“…Strabismus (an eye turn), anisometropia (differences in refractive errors), or other causative factors, which occlude the visual axis (form deprivation), 1 can challenge the visual system with differing patterns of visual acuity (VA) and contrast sensitivity losses. 3,4 There is increasing attention now, on the critical role interocular suppression has among amblyopes. [5][6][7][8] Rather than adhering to a traditional monocular therapy in the form of occlusion or penalization, which is challenged by high reoccurrences of residual amblyopia, 9,10 we now aim to provide a proper binocular visual experience during therapy.…”
mentioning
confidence: 99%
“…Although amblyopia is typically regarded as a disorder of spatial vision, a number of studies have identified deficits in motion perception that appear to be independent of impairments of form perception (see Thompson et al, 2011 for a recent overview). Many of the motion deficits that have been reported are consistent with abnormalities at the level of hMT+ complex.…”
Section: A Motion Deficit In Amblyopia?mentioning
confidence: 99%